Theoretical studies on the oxidized cellulose fibers interactions with zwitterionic drugs - Barros, Júlio Ortiz Amando de (2021)
Cellulose is the main component of wood and it is known as the most abundant organic molecule in our planet. The great variety of sub products of cellulose, considering physical and chemical treatments, makes it a great promise material for a green future. In this work we focused in the usage of cellulose for wound healing applications. The oxidized cellulose fibers (OCF) are widely used as a hemostatic materials, and some amino acids have reparative and anti microbial effects. The amino acids adsorption on OCF was measured by Zimnitsky et. al. in 2006, the most and less adsorbed amino acids were tryptophan and proline respectively. Motivated by this article, the adsorption of these two amino acids on the surface of OCF was studied, and computational simulation techniques were used to give theoretical insights of this process. Both classical and quantum mechanics calculations were performed in order to better understand the factors that interfere in the adsorption process. The main analyzed points were related to the proton transfer from the OCF to the amino acid molecules, the oxidation degree of the OCF, and the differences between the tryptophan and proline adsorption. It was observed that the adsorption is favoured in protonated molecules, resulting in a greater number of adsorbed molecules and with a better stability. The modified groups showed to be a limiting factor for the adsorption, when there are more oxidized groups than amino acid molecules the total adsorption can be achieved for protonated molecules, but in the opposite case the adsorption is impaired. Finally, the adsorption of proline and tryptophan molecules had many differences, the main ones being: the indication that tryptophan is less probable to be protonated, but the protonation affects more the proline adsorption; and that proline adsorption is more dependent on the oxidation degree, resulting in a larger decrease than tryptophan when the number of amino acid molecules is greater than the number of oxidized groups.